7(3x-15)=4(5-x)

Simple and best practice solution for 7(3x-15)=4(5-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3x-15)=4(5-x) equation:


Simplifying
7(3x + -15) = 4(5 + -1x)

Reorder the terms:
7(-15 + 3x) = 4(5 + -1x)
(-15 * 7 + 3x * 7) = 4(5 + -1x)
(-105 + 21x) = 4(5 + -1x)
-105 + 21x = (5 * 4 + -1x * 4)
-105 + 21x = (20 + -4x)

Solving
-105 + 21x = 20 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-105 + 21x + 4x = 20 + -4x + 4x

Combine like terms: 21x + 4x = 25x
-105 + 25x = 20 + -4x + 4x

Combine like terms: -4x + 4x = 0
-105 + 25x = 20 + 0
-105 + 25x = 20

Add '105' to each side of the equation.
-105 + 105 + 25x = 20 + 105

Combine like terms: -105 + 105 = 0
0 + 25x = 20 + 105
25x = 20 + 105

Combine like terms: 20 + 105 = 125
25x = 125

Divide each side by '25'.
x = 5

Simplifying
x = 5

See similar equations:

| 8x+7=4x+37 | | 6t+3(2+9t)+7= | | 10+2(10)= | | 3(2x-6)=6(1-x) | | 3x-2+x=10-2x | | 5(x+2)=4(9-2x) | | 3+5(5t+1)+8t= | | 4*a-2*1+11=6*a-13 | | 2(x+4)=3(6-x) | | 9*w-2*w+8=4*w+38 | | 3-6x=7-7x | | 7(x+4)=5(x-3) | | 2*m+6=2*m-1 | | (4m+3)9+6m= | | 6*n+21=4*n+57 | | 2+(6m+3)7= | | 6(x+1)=4(x-2) | | 9+9(5+4m)= | | 7(3x+3)=4(4x-1) | | 4+6(3m+2)= | | q+5=2*q+7 | | 3(4x+2)=2(5x-2) | | 4*x+11=x+2 | | 2(2x+3)=3(x+1) | | 6m+7(7m+9)= | | 3x-3=9-x | | 14*k+16*k+88=163 | | 2r-8+4=5(r+1) | | 23+x=2-2x | | 3(2x-4)=2(x-2) | | 3(1+4m)+5m= | | 5(x-2)=4(x-3) |

Equations solver categories